Evaluation of Secondary Disaster Criteria after Disaster: An Application for Ordu Province - İrem Gaferoğlu; Sude Kaya; Y. Baran Kalemler; Emel Güven; Tamer Eren (Doğal Afetler ve Çevre Dergisi)
Disaster; It is all of the events that take place beyond the control of people, cause deficiencies in ordinary life, are insufficient and losses occur as a result. Due to its geological location, Turkey often faces natural hazards. Floods, earthquakes, forest fires, landslides, avalanches, snow and storms are the most common natural hazards in Türkiye. Natural disasters can also cause secondary natural disasters in some cases. In this context, secondary disasters were discussed in the studies. One of the most common types of disasters in secondary disasters is landslide disaster. For this reason, considering the disasters experienced in the past, Ordu province, which has a high probability of landslides, was chosen as the application area. In addition, due to the dominant geological, topographic structure and meteorological conditions in the province, some regions have a structure that can cause secondary disasters. In the study, it was emphasized that the landslide disaster occurred as a secondary disaster in Ordu province after the natural disaster. Multi-Criteria Decision Making (MCDF) methods were used in problem solving. First of all, the criteria that may cause secondary disasters in Ordu province (high slope, meteorological factors, disaster type, mass movements, unplanned settlement, gravity effect) were created by literature search and weighted with the Analytical Hierarchy Process (AHP) method. Within the scope of the weighted criteria, 19 districts of Ordu were ranked according to the possibility of a landslide secondary disaster using the Technique for Order Preference By Similarity To An Ideal Solution (TOPSIS) method. The district with the highest probability of a landslide occurring as a secondary disaster was Mesudiye.